CLINICAL RESULTS OF ANTERIOR TWO-ROD PLATE SURGERY FOR THORACOLUMBAR SPINAL INJURY - TAKAHASHI, Kazuhisa; KITAHARA, Hiroshi; DEZAWA, Akira; INOUE, Shunichi; MINAMI, Shohei; YOSHINAGA, Katsunori (Rihabiritēshon igaku, 1987)
We examined 16 patients with thoracolumbar spinal injuries who underwent anterior decompression and fusion by surgical use of an aterior two-rod plate. The subjects were 15 men and one woman. Follow-up ranged from five to 21 months, with an average of 11.4 months. The injuries included ten burst fractures (T12:1, L1:5, L2:1, L3:1, and L4:2) and six dislocation fractures (T11-12:2, T12-L1:2, and L1-2:2). All the burst-fracture cases were neurologically incomplete, but five out of six dislocation-fracture cases showed complete neurological deficit below the spinal lesion. First we examined the local stability of the operated level and total mobility of the lumbar spine, using lateral bending and flexion-extension x-ray films. Scoliosis averaged 6.3 degrees prior to surgery. Although scoliosis improved to 2.6 degrees immediately after surgery, by follow-up it was back to 6.3 degrees. Average preoperative kyphosis of 23 degrees was reduced to 12.2 degrees immediately after surgery, but reverted to 17.9 degrees by follow-up. Dislocation-fracture cases lost more ground postoperatively and had greater deformities tan did the burst-fracture cases. Total mobility of the lumbar spine was evaluated according to two angles: (a) on the A-P view, the angle between the axis of L1 and a line connecting both iliac crests, and (b) on the lateral view, the angle between the axes of L1 and L5. We confirmed good mobility of the lumbar spine for every case, in both A-P and lateral views. Finally, in order to investigate postoperative progress in activities of daily living (ADL), we took serial assessments of the Barthel Index. Cases receiving the two-rod plate for burst fractures showed prompter recovery of ADL than cases of incomplete lesions treated by Luque instrumentation. The cases of dislocation fracture treated by two-rod surgery showed recovery curves resembling the recovery patterns of patients with complete lesions treated by Luque instrumentation. In our series, conservatively treated groups showed the slowest recovery of the Barthel Index, irrespective of completeness versus incompleteness of the lesion.